2019
DOI: 10.3889/oamjms.2019.516
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Quantitative Analysis of Betamethasone Valerate and Neomycin Sulfate Cream by High Performance Liquid Chromatography and Spectrophotometry

Abstract: BACKGROUND: Combination of betamethasone valerate and neomycin sulfate in cream is used to treat the itching, redness, dryness, scaling, inflammation and discomfort of various skin conditions caused by infection. The combination of active ingredients has side effects which can cause dry skin, thinning of the skin, hypertrichosis, and stretch marks. AIM: The purpose of this study was to make a formula containing vitamin E and quantitative analysis of betamethasone valerate and neomycin sulfate in creams u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…in 2019, the authors reported the quantitative analysis of betamethasone valerate and neomycin sulfate in creams using HPLC. However, the chromatogram exhibited disturbances between the peaks [12]. However, it is worth noting that none of these studies have reported the utilization of the QbD approach.…”
Section: Introductionmentioning
confidence: 99%
“…in 2019, the authors reported the quantitative analysis of betamethasone valerate and neomycin sulfate in creams using HPLC. However, the chromatogram exhibited disturbances between the peaks [12]. However, it is worth noting that none of these studies have reported the utilization of the QbD approach.…”
Section: Introductionmentioning
confidence: 99%